Perancangan Aplikasi Sumber dan Media Pembelajaran Berbasis Android bagi Guru dan Siswa Indonesia - Apit Fathurohman; Lintang Auliya Kurdiati; Esti Susiloningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Current technological advances, cellular phones or cellphones have been very developed so that they can be used in various fields, one of which is in the field of education which can be used as a source and educative learning media. In today's digital era, Indonesia also has several challenges in the field of education, one of which is that the majority of Indonesian students, especially those in elementary school, carry heavy books, which can interfere with their growth and health. The purpose of this research is to design and create a mobile phone application as a source and learning media that can be utilized by teachers, students or SMEs in the current digital era. This research uses R&D method using Rowntree development model. This ILTEC application provides several application modes, including student mode, teacher mode, student mode, and lecturer mode. Each mode has its own features that distinguish it from one mode to another. In student and student mode there are module features and learning media, while in teacher and lecturer mode there are RPP/RPS features, modules, and learning tools. Each of these features cannot be accessed freely by every user but must use the application coins owned by the user to be able to access